Foraminal Injection of a Painful Sacral Nerve Root Using an Epidural Catheter: Case Report. Issue 2 (1st March 2002) - Friedman, Robert; Li, Victor; Mehrotra, Deepak; Mosuro, Yusuf; Atkinson, Gary
Abstract : Background and Objectives: Nerve root pain has been treated with steroid injections since the 1970s. We will describe a novel method for nerve root injection using a directed epidural catheter. Case Report: A case is described where catheter placement accurately reproduced symptoms which were then relieved with local anesthetic and steroid. Conclusion: This is a novel approach to treatment of painful nerve roots with a catheter.